232k views
0 votes
For the graphed function f(x) = -(3)x1+3, calculate the average rate of change from x = 1 to x = 3.

-4
-2
2
4

For the graphed function f(x) = -(3)x1+3, calculate the average rate of change from-example-1
User Shanet
by
5.5k points

1 Answer

2 votes

Answer:

The average rate of change is -4

Explanation:

The given function is f(x) = -(3)x1+3

We want to find the average rate of exchange of this function from x=1 to x=3.

This is the slope of the secant line joining the points (1,f(1)) and (3,f(3)).

From the graph, f(1)=2 and f(3)= -6

The average rate of exchange

=f(3)-f(1)/3-1

=-6-2/3-1

=-8/2

=-4

User Vixez
by
5.4k points